2024
DOI: 10.1038/s41586-024-07278-3
|View full text |Cite
|
Sign up to set email alerts
|

The variation and evolution of complete human centromeres

Glennis A. Logsdon,
Allison N. Rozanski,
Fedor Ryabov
et al.

Abstract: Human centromeres have been traditionally very difficult to sequence and assemble owing to their repetitive nature and large size1. As a result, patterns of human centromeric variation and models for their evolution and function remain incomplete, despite centromeres being among the most rapidly mutating regions2,3. Here, using long-read sequencing, we completely sequenced and assembled all centromeres from a second human genome and compared it to the finished reference genome4,5. We find that the two sets of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 86 publications
(208 reference statements)
1
13
0
Order By: Relevance
“…This attribute is also reflected in our tomograms where we observe kinetochores of varied size and with varied distribution of kinetochore complexes. Specifically, the finding that CENP-A occupancy is often split between multiple regions within a single centromere (Altemose et al, 2022a; Dubocanin et al, 2023; Gershman et al, 2022; Logsdon et al, 2024; Sacristan et al, 2022) is consistent with our own observation that some kinetochores are comprised of a single chromatin clearing whereas others are comprised of 2-3 clearings. Each of the clearings likely corresponds to a region on the linear DNA sequence with a high local density of CENP-A nucleosomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This attribute is also reflected in our tomograms where we observe kinetochores of varied size and with varied distribution of kinetochore complexes. Specifically, the finding that CENP-A occupancy is often split between multiple regions within a single centromere (Altemose et al, 2022a; Dubocanin et al, 2023; Gershman et al, 2022; Logsdon et al, 2024; Sacristan et al, 2022) is consistent with our own observation that some kinetochores are comprised of a single chromatin clearing whereas others are comprised of 2-3 clearings. Each of the clearings likely corresponds to a region on the linear DNA sequence with a high local density of CENP-A nucleosomes.…”
Section: Discussionsupporting
confidence: 90%
“…These DNA sequencing-based results align remarkably well with our findings where tomograms show kinetochore complexes clustered within a distinct clearing space composed of open chromatin. Sequencing maps of human centromeres have also shown that CENP-A occupancy is highly variable in both magnitude and distribution, not only among individuals but also among chromosomes within an individual (Altemose et al, 2022a; Gershman et al, 2022; Logsdon et al, 2024). This attribute is also reflected in our tomograms where we observe kinetochores of varied size and with varied distribution of kinetochore complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the rDNA array in macaques is only found in chromosome 10, in contrast to humans, where they are located in five chromosomes 15,121 (chr13, chr14, chr15, chr21, and chr22) (Figure 1e). Third, the length and composition of the α-satellite arrays differ between macaques and apes 18,24,49 . Additionally, while the α-satellite arrays are relatively conserved within macaques, they exhibit greater variability in humans 18,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, the length and composition of the α-satellite arrays differ between macaques and apes 18,24,49 . Additionally, while the α-satellite arrays are relatively conserved within macaques, they exhibit greater variability in humans 18,24 . Finally, 91 large-scale genomic differences between macaques and humans have been revealed at single-base resolution, most of which are associated with centromere repositions, inversion, and translocation 47,92,93 (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation